On p?-dual spaces of generalized difference sequence spaces - Et, Mikail; Isik, Mahmut (Pergamon-Elsevier Science Ltd, 2012)
In this paper, we compute the p alpha-, p beta- and p gamma-duals of the sequence spaces l(infinity) (k(m)), c (k(m)), co (k(m)), the pN-dual of the sequence spaces Delta(m)(v, r)(l(infinity)) and the p alpha-dual of the sequence spaces Delta(m)(v, r)(l(infinity)), Delta(m)(v,r)(c) and Delta(m)(v,r)(c(0)). (c) 2011 Elsevier Ltd. All rights reserved.
Keywords: Difference sequence spaces; p alpha-, p beta-, p gamma and pN-dual